SYNTHESIS AND OPTICAL PROPERTIES OF LIGANDS BASED ON FERROSENILATSETON - Sulaymonova ZilolaAbduraxmanovna; Navruzova Mashhura Baxtiyor qizi (Scientific Impulse, 2024)
We obtained fl-diketone - l-ferrocenylbutanedione-1,3 by Claisen condensation. Ligands - hydrazones o f monocarboxylic acids l-ferrocenylbutanedione-1,3 (H2L) were synthesized by the interaction o f carboxylic acid hydrazides with ferrocenoylacetone. The optical properties o f all compounds synthesized in the work have been studied; based on the absorption spectra data, the values o f the optical band gap were determined; it was shown that all the synthesized compounds are d-п type chromophores and have a band gap o f 1,39-2,26 eV, i.e. they belong to narrow-gap semiconductors.